A Case of Nonpuerperal Uterine Inversion Caused by Cervical Cancer. (31st January 2022) - Hiratsuka, Daiki; Tsukazaki, Takehiro; Sone, Kenbun; Neriishi, Kazuaki; Takechi, Kimihiro
Abstract : Uterine inversion is a rare puerperal event in the third stage of labor. Nonpuerperal uterine inversion is even rarer and is mainly caused by uterine fibroids, uterine sarcoma, or endometrial cancer. This is the first report of uterine inversion caused by cervical cancer. A 67-year-old woman presented with a 10 cm pelvic mass. Contrast-enhanced magnetic resonance imaging revealed uterine inversion, which was preoperatively diagnosed to be caused by endometrial cancer and was treated using an extended abdominal hysterectomy. Postoperative histopathological examination revealed that the primary tumor was a squamous cell carcinoma with coexistent high-grade squamous intraepithelial lesions and small-cell neuroendocrine carcinoma. Immunostaining was diffusely positive for p16 and negative for estrogen receptors. The postoperative diagnosis was cervical squamous cell carcinoma. Our observations suggested that cervical carcinoma can cause uterine inversion by invading the corpus.